Penerapan Metode Promethee Dalam Rekomendasi Pemilihan Karyawan Berprestasi - Dimas Aulia Trianggana; Indra Kanedi (UNIVED Press, 2024)
In every company there is an employee performance assessment system that is used to find out who can be used as role models as outstanding employees. The assessment aspects are divided into 4 categories, namely Discipline, Work Attitude, Potential and Ability, and Work Results. In this decision support system the Promethe method has been applied, so that the final assessment results for each employee have gone through the Promethe method calculation procedure. The final assessment results of the Promethee Method will be sorted from the highest value to the lowest value with two conditions where if the Net Flow value is all 0 then it will be sorted based on the leaving flow and entering flow values, but if the Net Flow value is not all 0, then it will be sorted based on Net Flow value obtained from each employee